THE REAL PRACTICE-ORIENTED INSTRUCTIONAL ENGINEERING AS A FACTOR OF DEVELOPMENT AND FORMATION OF STUDENTS' PROFESSIONAL COMPETENCE - Tatiana M. Plekhanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Modernization of the system of higher education requires the involvement of the process of preparation of bachelors practitioners - representatives of the professional business environ-ment. The article deals with one of the forms of interaction with these specialists - attraction to cooperation of university graduates. The main aim of the present study is to clarify how the joint work of the teaching staff and former students affects the quality of training of students. As a result of the experiment, it can be concluded that the inclusion of the management train-ing of students representatives of the business environment enables students to develop the skills of professional business communication, to give them the opportunity to solve real pro-fessional problems to prepare for the future professional activities and to facilitate the process of entering a business professionals